“It was too much for me”: mental load, mothers, and working from home during the COVID-19 pandemic - Delaney, Caitriona; Bobek, Alicja; Clavero, Sara (Frontiers in Psychology, 2023)
This study analyses the experiences of working from home (WfH) during the COVID-19 pandemic and the impact it has on working mothers through the lens of “mental load.” Remote study, often lauded as a way to reduce work/life conflicts, can bring new multifaceted challenges for working mothers and, as this study shows, suddenly shifting to remote work led to the boundaries among work, care, and domestic labour becoming blurred. The data used here are from narrative interviews collected as part of the RESpondIng to outbreakS through co-creaTIve inclusive equality stRatEgies (RESISTIRÉ) Horizon 2020 project, which analyses the impact of COVID-19 policies on gendered inequalities across the EU27 and Türkiye, Serbia, UK, and Iceland. We draw on 12 narratives from working mothers in Austria, Bulgaria, Czechia, Denmark, Ireland, Estonia, Greece, Portugal, Netherlands, the United Kingdom, and Slovakia. Employing thematic analysis, the analysis of these narratives, illuminates the challenges and opportunities of WfH and highlights its impact on mental load. While adding to the research on WfH and working mothers, the analysis also illustrates the lessons to be taken forward as well as underscoring the importance of mental load both theoretically and empirically.